Are the biological effects of ethanol due to primary interactions with lipids or with proteins? - Franks,NP; Lieb,WR (Alcohol Alcohol Suppl, 1987)
The biological effects of ethanol and other simple organic molecules have traditionally been ascribed to their actions on the lipid portions of biological membranes. However, at the concentrations at which these molecules exert their pharmacological effects in man and other animals, changes in the structure and fluidity of lipid bilayers are extremely small and can be mimicked by a change in temperature of only about 1 degree C. On the other hand, we have found that the activity of a soluble protein can be markedly affected at these concentrations. Indeed, the concentrations of general anaesthetics which half-inhibit the activity of this enzyme are essentially identical to those which cause general anaesthesia in animals. The evidence thus suggests that ethanol and other simple molecules act directly on proteins rather than lipids.